Prosecuting Corporations for Genocide. - Kelly, Michael J.
1 online resource (281 pages)
Keywords: Prosecuting Corporations for Genocide explains how multinational corporations should be criminally liable for their role in financing or otherwise supporting atrocities like genocide. This book demonstrates how international criminal jurisdiction should be extended over corporations for atrocities and makes the case that it should be done promptly.